Lithium-doped two-dimensional perovskite scintillator for wide-range radiation detection - Xie, Aozhen (2023)
Two-dimensional lead halide perovskites have demonstrated their potential as high-performance scintillators for X- and gamma-ray detection, while also being low-cost. Here we adopt lithium chemical doping in two-dimensional phenethylammonium lead bromide (PEA)2PbBr4 perovskite crystals to improve the properties and add functionalities with other radiation detections. Li doping is confirmed by X-ray photoemission spectroscopy and the scintillation mechanisms are explored via temperature dependent X-ray and thermoluminescence measurements. Our 1:1 Li-doped (PEA)2PbBr4 demonstrates a fast decay time of 11 ns (80%), a clear photopeak with an energy resolution of 12.4%, and a scintillation yield of 11,000 photons per MeV under 662 keV gamma-ray radiation. Additionally, our Li-doped crystal shows a clear alpha particle/gamma-ray discrimination and promising thermal neutron detection through 6Li enrichment. X-ray imaging pictures with (PEA)2PbBr4 are also presented. All results demonstrate the potential of Li-doped (PEA)2PbBr4 as a versatile scintillator covering a wide radiation energy range for various applications.